2020
DOI: 10.1016/j.jeurceramsoc.2020.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Direct Integration of Cold Sintered, Temperature-Stable Bi2Mo2O9-K2MoO4 Ceramics on Printed Circuit Boards for Satellite Navigation Antennas

Abstract: Bi2Mo2O9-K2MoO4 (BMO-KMO) composite ceramics with >95% theoretical density were densified by cold sintering at 150 °C. XRD, Raman, back-scattered SEM and EDX spectroscopy indicated that the BMO and KMO phases coexisted in all composites without inter-diffusion and secondary phases. Temperature coefficient of resonant frequency with near-zero value ~ -1 ppm/°C was acheived for BMO-10%KMO with pemittivity ~ 31 and quality factor ~ 3,000 GHz.Cold-sintered composite ceramics were directly pressed/integrated onto a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…Despite recent advances, the sintering temperatures of LTCCs and ULTCCs are still much higher than can be withstood by a polymer-based printed circuit boards (PCBs < 200 °C), which inhibits the development of integrated, directly packaged RF devices and systems. CSCCs are a series of ceramics or ceramic composites that can be densified at ultralow temperatures < 200 °C by the cold sintering process (CSP) [3,[42][43][44][45][46][47][48][49], which enables not only co-firing with base-metal electrodes [3,50,51] but also PCBs [52] and polymers [43,53]. Along with CSCCs for RF applications, cold sintering has also been employed to densify ferroelectrics [54][55][56][57][58], piezoelectrics [59][60][61][62][63], thermoelectrics [64], semiconductors [65][66][67][68][69][70], electrolytes [71][72][73][74][75], cathodes [76,77] and oxides [78][79][80][81][82], which are widely used in many applic...…”
Section: Invited Feature Paper-reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recent advances, the sintering temperatures of LTCCs and ULTCCs are still much higher than can be withstood by a polymer-based printed circuit boards (PCBs < 200 °C), which inhibits the development of integrated, directly packaged RF devices and systems. CSCCs are a series of ceramics or ceramic composites that can be densified at ultralow temperatures < 200 °C by the cold sintering process (CSP) [3,[42][43][44][45][46][47][48][49], which enables not only co-firing with base-metal electrodes [3,50,51] but also PCBs [52] and polymers [43,53]. Along with CSCCs for RF applications, cold sintering has also been employed to densify ferroelectrics [54][55][56][57][58], piezoelectrics [59][60][61][62][63], thermoelectrics [64], semiconductors [65][66][67][68][69][70], electrolytes [71][72][73][74][75], cathodes [76,77] and oxides [78][79][80][81][82], which are widely used in many applic...…”
Section: Invited Feature Paper-reviewmentioning
confidence: 99%
“…Most importantly from a manufacturing perspective, Wang et al [52] have demonstrated that cold-sintered, temperature stable 0.9BMO-0.1KMO (30 × 30 × 7 mm, ε r ~ 31) could be directly pressed onto PCBs (T M < 200 °C) with a satellite navigation antenna subsequently fabricated using the standard Cu metallization as the ground plane, as shown in Fig. 14A [52]. No chemical reaction/delamination was observed at the interface between ceramic and Cu layers, as shown in the SEM images and EDS elemental line-scans in Fig.…”
Section: Rf Devicesmentioning
confidence: 99%
“…However, silicate-based ceramics are conventionally sintered at high temperatures (> 1200 °C), consuming energy and releasing carbon. The cold sintering process (CSP) can densify ceramics and composites at ultralow temperatures (< 200 °C), temperatures that not only reduce carbon emissions but also facilitate direct deposition onto printed circuit boards [15][16][17][18][19][20][21][22][23][24][25][26][27] . CaSnSiO5 (CSSO) is conventionally sintered at 1450 °C with εr ~ 10.9, τf ~ 35 ppm/°C, Q×f ~ 43600 GHz [28,29] and is therefore, an ideal base to begin the search for cold sintered silicates.…”
Section: Introductionmentioning
confidence: 99%
“…CaSnSiO5 (CSSO) is conventionally sintered at 1450 °C with εr ~ 10.9, τf ~ 35 ppm/°C, Q×f ~ 43600 GHz [28,29] and is therefore, an ideal base to begin the search for cold sintered silicates. However, initial cold sintering studies of CSSO were unsuccessful and hence, following work by Wang and co-workers [26,27] , K2MoO4 (KMO) was used as a fluxing agent to encourage densification and to tune τf to near zero. The microstructure, Ag compatibility and microwave dielectric properties of CSSO-KMO composites were therefore, investigated followed by the design, fabrication and testing of a prototype microstrip patch antenna on substrates made from optimum compositions.…”
Section: Introductionmentioning
confidence: 99%
“…For stable materials that generally dissolve incongruently in water, a proactive mixture of solvochemical solutions must be used. 12,15,16 In addition, it's also a research hotspot to fabricate novel composite ceramics through the CSP, such as microwave composite ceramics with high quality factors for wireless and satellite communication technology, [17][18][19][20][21] three-dimensionally (3D) integrated multilayer ceramic capacitors with alternating ceramic and metal electrode layers, 22 and novel dielectric materials with fast signal response performance that meets the requirements of the rapid development of the h-generation mobile cellular network (5G). 23,24 To obtain dense barium titanate (BaTiO 3 ) ceramics, a water-based suspension of Ba(OH) 2 and TiO 2 was used to avoid incongruent dissolution of BaTiO 3 during the CSP.…”
Section: Introductionmentioning
confidence: 99%